Do governance networks build collaborative capacity for sustainable development? Insights from Solomon Islands - Blythe, Jessica; Cohen, Philippa J.; Eriksson, Hampus; Harohau, Daykin (Springer, 2022)
To build capacity for addressing complex sustainable development challenges, governments, development agencies, and non-governmental organizations are making substantial investments in governance networks. Yet, enthusiasm for establishing governance networks is not always matched by empirical evidence on their effectiveness. This gap challenges these groups to know whether investing in governance networks is worth their time and effort; a weighing-up that is particularly critical in contexts of limited resources. Through a qualitative case study in Solomon Islands, we evaluate the extent to which a governance network, called the Malaita Provincial Partners for Development, contributed to four dimensions of collaborative governance capacity: individual, relational, organizational, and institutional. We find that the network made moderate contributions to individual, relational and organizational capacity, while institutional capacity remained low despite the presence of the network. Based on these findings, we argue that governance networks are not a panacea. Continued efforts are needed to establish when, how, and in what contexts collaborative networks are effective for building collaborative capacity for sustainable development.